Doxycycline Therapy for Abdominal Aortic Aneurysm: Inhibitory Effect on Matrix Metalloproteinases - Paghdar, Smit (Cureus, 2021)
Abdominal aortic aneurysm (AAA) is a life-threatening condition associated with smoking, aging, atherosclerosis, and destruction of the connective tissue in the abdominal aortic wall. Disturbances in the synthesis and degradation of matrix metalloproteinase (MMP) have been known to contribute to the development of AAAs. The only available treatment of AAA is surgical repair. Doxycycline, a tetracycline analog, is thought to have an inhibitory effect on MMPs. Knowing the effect of doxycycline, there may be some favorable effects of the drug to reduce the growth of small AAAs and avoid the need for invasive treatment. This article aims to determine the relationship between doxycycline and the MMPs to prevent the growth of small AAAs. We conducted our review using online resources such as PubMed, Google Scholar, The Journal of Vascular Surgery, and ResearchGate. The result of our study supports the effect of doxycycline in preventing the growth of small AAAs. We conclude that therapeutic treatment with doxycycline in patients with small AAAs can prevent the growth of aneurysms, life-threatening aneurysm rupture, and reduce the need for expensive, invasive treatment.